Fundamentals of Entrepreneurship (ENT300) : Case study Hannan Medispa / Azzatul Natasha Ahmad … [et al.] - Ahmad, Azzatul Natasha; Afandi, Dyg Afiqah Shafira; Harmy, Nur Sabrina Natasha (2019)
The case study is to identify the company's background, services, company's analysis, business problem and the recommendation that can be use for the improvement of the company. The methods that used to study the analysis is by interview with the management of the company.